Synthesis and inhibitory evaluation of 3-linked imipramines for the exploration of the S2 site of the human serotonin transporter. Issue 12 (15th June 2016) - Brinkø, Anne; Larsen, Maja T.; Koldsø, Heidi; Besenbacher, Louise; Kolind, Anders; Schiøtt, Birgit; Sinning, Steffen; Jensen, Henrik H.
Graphical abstract: Abstract: The human serotonin transporter is the primary target of several antidepressant drugs, and the importance of a primary, high affinity binding site (S1) for antidepressant binding is well documented. The existence of a lower affinity, secondary binding site (S2) has, however, been debated. Herein we report the synthesis of 3-position coupled imipramine ligands from clomipramine using a copper free Sonogashira reaction. Ligand design was inspired by results from docking and steered molecular dynamics simulations, and the ligands were utilized in a structure–activity relationship study of the positional relationship between the S1 and S2 sites. The computer simulations suggested that the S2 site does indeed exist although with lower affinity for imipramine than observed within the S1 site. Additionally, it was possible to dock the 3-linked imipramine analogs into positions which occupy the S1 and the S2 site simultaneously. The structure activity relationship study showed that the shortest ligands were the most potent, and mutations enlarging the proposed S2 site were found to affect the larger ligands positively, while the smaller ligands were mostly unaffected.